(untitled) (Research, Society and Development, 2022)
Longing for the formation of young people as critical, autonomous, and responsible individuals, a more dynamic approach of the contents of Nature Science appears as an urgency in the current teaching context. On the one hand, we have the teacher, who needed to reinvent oneself and adapt to new technologies to teach their classes remotely; on the other hand, we have the student in the same need for adaptations with a complicator, which is maintaining eating habits quality in this context. This research was, guided by the following question: To what extent can the purposes of a healthier and more sustainable diet contribute to a more meaningful Chemistry teaching? The overall objective of this study is to analyse a didactic sequence based on the Three Pedagogical Moments for the study of chemical concepts contextualized through the theme of healthy and sustainable eating habits. The pedagogical proposal was developed in six remote meetings, through the Google Classroom platform, with fifty-eight third grade high-school students from a Public State School in Rio Grande do Sul, Brazil. To investigate the relevance of the didactic sequence, qualitative research was, carried out and for the data, collection it was applied a logbook and videos made by students during the didactic intervention. With the application of the didactic sequence, it could be, observed a contribution to the improvement of the chemistry teaching and learning process, as the appliance of the mentioned educational product made it possible for the students to become protagonists of the construction of scientific knowledge.